Proteome Analysis of Coinfection of Epithelial Cells with Filifactor alocis and Porphyromonas gingivalis Shows Modulation of Pathogen and Host Regulatory Pathways - Aruni, A. Wilson (American Society for Microbiology, 2014)
Changes in periodontal status are associated with shifts in the composition of the bacterial community in the periodontal pocket. The relative abundances of several newly recognized microbial species, including Filifactor alocis, as-yet-unculturable organisms, and other fastidious organisms have raised questions on their impact on disease development. We have previously reported that the virulence attributes of F. alocis are enhanced in coculture with Porphyromonas gingivalis. We have evaluated the proteome of host cells and F. alocis during a polymicrobial infection. Coinfection of epithelial cells with F. alocis and P. gingivalis strains showed approximately 20% to 30% more proteins than a monoinfection. Unlike F. alocis ATCC 35896, the D-62D strain expressed more proteins during coculture with P. gingivalis W83 than with P. gingivalis 33277. Proteins designated microbial surface component-recognizing adhesion matrix molecules (MSCRAMMs) and cell wall anchor proteins were highly upregulated during the polymicrobial infection. Ultrastructural analysis of the epithelial cells showed formation of membrane microdomains only during coinfection. The proteome profile of epithelial cells showed proteins related to cytoskeletal organization and gene expression and epigenetic modification to be in high abundance. Modulation of proteins involved in apoptotic and cell signaling pathways was noted during coinfection. The enhanced virulence potential of F. alocis may be related to the differential expression levels of several putative virulence factors and their effects on specific host cell pathways.